If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2x = 28 + 2x Solving -2x = 28 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -2x + -2x = 28 + 2x + -2x Combine like terms: -2x + -2x = -4x -4x = 28 + 2x + -2x Combine like terms: 2x + -2x = 0 -4x = 28 + 0 -4x = 28 Divide each side by '-4'. x = -7 Simplifying x = -7
| 18x-12+24= | | x^2+14x+480=0 | | 5t=howmanylb | | 68=5 | | w(w-7)=78 | | 80/1/4 | | 98=w+23 | | (8x)/(2x)=0 | | 5x+11y=146 | | 8x/2x=0 | | 4=c-3 | | S-1=8 | | 7=F+1 | | 5(x+6)-7x=36 | | y=(x+3)(x+1)(x+1)(x-1)(x-1)(7+3i)(7-3i) | | (9-x)/5=3 | | 16x^2-72x=0 | | 4m+7=43.8+7 | | x+(x*0.13)=56.70 | | x+(x*.15)=56.70 | | 3x=2x+12 | | 10x=125 | | x*.15=56.70 | | 26=g+7 | | r^2+5r-9=0 | | 58/180 | | -2x-2=2 | | 3y-9=8x | | 10x-116=5x-6 | | 1.6=0+5T^2 | | x-3=4-2x | | 2X+2Y=730 |